The Code of the City of Atlanta 164 (William T. Newman ed., 1879) - (:unkn) unknown (My University, 1879)
Ch. 42-Powder, §§ 462-464: The council shall have the discretion to grant or refuse a license. Salesmen of gunpowder shall have a sign saying they are licensed to sell. Also prohibited burning rockets, crackers, or any kind of fire-works in Atlanta.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER